Uncertainty Quantification of Leading Edge Erosion Impacts on Wind Turbine Performance. Issue 5 (September 2020) - Maniaci, David C.; Westergaard, Carsten; Hsieh, Alan; Paquette, Joshua A.
Abstract: Many factors that influence the effect of leading edge erosion on annual energy production are uncertain, such as the time to initiation, damage growth rate, the blade design, operational conditions, and atmospheric conditions. In this work, we explore how the uncertain parameters that drive leading edge erosion impact wind turbine power performance using a combination of uncertainty quantification and wind turbine modelling tools, at both low and medium fidelity. Results will include the predicted effect of erosion on several example wind plant sites for representative ranges of wind turbine designs, with a goal of helping wind plant operators better decide mitigation strategies.